Inertia forces and moments balancing in robot manipulators: a review. (18th July 2017) - Arakelian, Vigen
Abstract: The balancing of linkages is an integral part of the mechanism design. Despite its long history, mechanism balancing theory continues to be developed and new approaches and solutions are constantly being reported. Hence, the balancing problems are of continued interest to researchers. Several laboratories around the world are very active in this area and new results are published regularly. In recent decades, new challenges have presented themselves, particularly, the balancing of robots for fast manipulation. Various design concepts and methods for balancing of robot manipulators are available in the literature. The author believes that this is an appropriate moment to present the state of the art of the studies devoted to balancing of robot manipulators and to summarize their research results. Thus, the aim of this paper is to propose a review of shaking force and shaking moment balancing methods used in robotics, in particular, for serial and parallel architectures. The described methods are arranged into two principal parts: the resultant inertia force (shaking force) balancing and the resultant inertia moment (shaking moment) balancing. Then each part is divided into subgroups according to features of balancing methods and illustrated via kinematic schemes. At the end of the paper, the balanced robot manipulators having particular structures, the balancing taking into account the payload, the reactionless space robots and the optimization methods used in the balancing of robot manipulators are discussed.